A Comparative Study of Hospital and Healthcare Standards 5th Edition 2022 and Program and Disease Specific Standards 2020 of the Healthcare Accreditation Institute, Thailand: Comparison of Hospital and Healthcare Standards 5th edition and Program and Disease Specific Standard 2020 - อินทรแสน วริศรา; ฉันทไกรวัฒน์ เยาวพา; พรหมพลุ้ย ตรีรัตน์; หล่อโลหชาญ ณัฐพล; ทองอินทร์ มาลินี (Journal of Health Science of Thailand, 2024)
Patient safety is important. Most healthcare facilities in Thailand have developed service systems in accordance with the hospital and health service standards of the Healthcare Accreditation Institute since 1996, which is currently in the 5th edition (2022), and there are many medical facilities that developed specialize care, thus leading to the development of disease-specific/system-specific standards in 2020. The objective of this study was to compare the differences between the two standards, divided into four areas: (1) qualifications to apply for the standard certification, (2) number and details of the requirements, (3) documents used for requesting certification, and (4) consideration criteria. The study showed that (1) requesting the disease-specific/system-specific standards hospitals was required to pass the accreditation level 2 or higher or equivalent to level 1 or higher of hospital and health service standards; (2) the number and details of hospital standard requirements for both standards consisted of 4 important parts, but hospital and health service standards had more requirements; (3) documents required for certification were similar, but the disease-specific/system-specific standards had more depth of contents; and (4) the criteria for consideration use the same criteria, but disease specific standards in Part III (patient care process) should have a score greater than 3.0. Healthcare facilities that want to apply for diseasespecific/ system-specific standards certification in 2020, should start from (1) defining the disease/ system that is the organization’s excellence; (2) setting up a working group for implementation; (3) setting the desired results, goals, and benchmarks; (4) operating, monitoring and reviewing the system for at least 3 years; and (5) facilitating the development by academic work.